Post-outburst radio spectral evolution of Cygnus X-3 - Miller-Jones, J; Blundell, K; Rupen, M; Beasley, A; Mioduszewski, A (Centre for Space Physics, 2003)
Multifrequency VLA and OVRO observations of the radio outburst of Cygnus X-3 in September 2001 are presented, illustrating the evolution of the spectrum of the source over a period of six days. An estimate of the magnetic field in the emitting region is made from the spectral turnover and possible explanations for the spectral evolution are suggested.